Pendampingan GENIUS: Gerakan Nutrisi Dan Psikologi Untuk Anak Sehat Dalam Pencegahan Stunting Berbasis Komunitas Di Desa Tanjung Hilir Kecamatan Lumbis - Cici Ismuniar Undunsyah; Nazwa Manurung; Nur Indah Noviyanti (Jurnal Dedikasi untuk Negeri, 2024)
Stunting is a chronic nutritional problem that hinders both physical and cognitive growth in children. It occurs due to a lack of proper nutritional intake during the first 1,000 days of a child’s life, from pregnancy to two years of age. In Tanjung Village, located in Nunukan Regency, North Kalimantan, stunting has become a serious issue, with a prevalence rate reaching 30%. Several key factors contributing to stunting in Tanjung Village include low economic conditions, limited parental education, restricted access to healthcare, poor sanitation, and early marriage/teen pregnancy. The impacts of stunting include stunted physical growth, cognitive impairments, and long-term health risks. The Nunukan Regency Government has implemented various efforts to combat stunting, such as nutrition supplementation programs, nutrition education, improved healthcare access, and sanitation programs. These efforts continue to be pursued to this day. As a proposed solution to prevent stunting, a holistic, community-based intervention program could be implemented. This program integrates nutrition education and psychosocial support education by providing information on parenting practices and facilitating the utilization of local resources, such as processing food from pisang kapok (local bananas). The result of this program is an improvement in the community’s knowledge regarding the educational topics delivered.